The effect of finance, infrastructure and training on the performance of Small and Medium Scale Enterprises (SMEs) in Nigeria. - Mohammed Sani, Abdullahi; Puspa Liza, Ghazali; Zainudin, Awang; Izah, Mohd Tahir; Nor Azman, Mat Ali @ Salim (2015)
Small and Medium Scale Enterprises (SMEs) play significant roles in providing employment opportunities, alleviating poverty, empowering communities, provision of goods and services, contributing toward the GDP, and achieving sustainable growth and development of the Nigerian economy. The aims of this research is to examine the effect of finance, infrastructure, and training on the performance of SMEs in Nigeria. This study used Kano State as a case study, and descriptive survey research design was used in this study. Sample size of 310 SMEs was drawn through simple random sampling out of the population of 1530 registered SMEs in Kano State, Nigeria. Primary data was employed in this study, and the data was collected through administering of close-ended structured questionnaires, but only 299 respondents respond to the questionnaires that were used for this study analysis. Statistical Package for Social Science (SPSS) software was used to analyze the respondent’s profile while Structural Equation Modeling (SEM) through Analysis of Moment Structure (AMOS) software was used to test the hypotheses of this study. The findings indicate that finance, infrastructure, and training have a positive and significant effect on the performance of SMEs in Nigeria. This suggests that there is a dire need for finance, infrastructure, and training to be given adequate concentration as they serve as the engine of boosting the performance of SMEs in Nigeria. Thus, it is recommended that the Government should undertake policy development work aimed at making access to fund easier for SMEs with growth potential and reduce the interest rate. The existing infrastructural facilities such as road, electricity, water supply, and telecommunication should be improved to a high standard by the Government. The Government should also encourage the SMEs entrepreneurs to make use of Entrepreneurial Development Programme (EDP) that is aimed at improving the skill level in the SMEs sector, and the SMEs entrepreneurs should inculcate the habit of training and developing their management and workforce in order to build a strong capacity for meeting these challenges.